Hak Pejalan Kaki yang Diambil Pengendara Sepeda Motor di Trotoar - Yesinta Yesinta; Irwansyah Irwansyah (Dakwatussifa: Journal of Da'wah and Communication, 2023)
Pedestrian is a term of transportation used to describe someone who walks on pedestrian paths, such as on sidewalks, on the side of the road or on special paths for pedestrians. One of the lanes that are often used by pedestrians is the sidewalk, where the sidewalk is a lane for pedestrians that is located in the area of ​​road use, is given a surface layer, is given a height higher than the surface of the sidewalk, and parallel to it is a lane for vehicles to provide pedestrian services. feet to increase safety, smoothness, and also comfort on the road. Most of the sidewalks have changed functions that are not in line with their main function as roads for pedestrians. One that we often see is street vendors or what is often called foot vendors selling on the sidewalks and motorbike riders sunning the sidewalks, thus endangering pedestrians and causing accidents. In this study aims to understand whether the sidewalk that should be used by pedestrians functions according to its actual function. In this study using interview methods and questionnaires. In this study the method used was the interview method or also called the interview where the interview is an event or process of interaction between the interviewer and also the person being asked where the results of the answers become a source of information. Questionnaire is one method of data collection that is used by asking a series of questions addressed to respondents to be answered. The research location is Jln William Iskandar, the sidewalk is right in front of the State Islamic University of North Sumatra. The results of a road pavement survey conducted by the State Islamic University of North Sumatra revealed that there were many violations of the function of road pavements committed by motorcyclists. Keywords: Motorcyclist, Pedestrian, Sidewalk